Cardiac Surgery Compared With Antibiotics Only in Patients Developing Infective Endocarditis After Transcatheter Aortic Valve Replacement. Issue 17 (4th September 2018) - Mangner, Norman; Leontyev, Sergey; Woitek, Felix J.; Kiefer, Philipp; Haussig, Stephan; Binner, Christian; Mende, Meinhard; Schlotter, Florian; Stachel, Georg; Höllriegel, Robert; Hommel, Jennifer; Binner‐Oussenek, Katrin; et al.
Abstract : Background: Infective endocarditis (IE) after transcatheter aortic valve replacement is a devastating complication associated with a high mortality. Our objective was to determine the impact of cardiac surgery (CS) and antibiotics (IE‐CS) compared with medical treatment with antibiotics only (IE‐ABx) on 1‐year mortality in patients developing IE after transcatheter aortic valve replacement. Methods and Results: Patients developing IE after transcatheter aortic valve replacement were included in this retrospective analysis. All‐cause 1‐year mortality was the primary end point. A total of 20 patients underwent IE‐CS compared with 44 patients treated by IE‐ABx. In this unmatched cohort, patients treated by IE‐ABx were older ( P =0.006), had a higher Society of Thoracic Surgeons score ( P =0.029), and more often had severe chronic kidney disease ( P =0.037). One‐year mortality was not different between groups (IE‐CS versus IE‐ABx, 65% versus 68.2%; P =0.802). The rate of any complication during treatment was higher in the IE‐CS group ( P =0.024). In a matched cohort, baseline characteristics were not significantly different. All‐cause 1‐year mortality was not different between groups (IE‐CS versus IE‐ABx, 65% versus 75%; P =0.490). A Cox regression analysis revealed any indication for surgery (hazard ratio, 6.20; 95% confidence interval, 1.80–21.41; P =0.004), sepsis on admission (hazard ratio, 4.03; 95% confidence interval, 1.97–8.24; P <0.001), and mitral regurgitation ≥2 (hazard ratio, 2.91; 95% confidence interval, 1.33–6.37) as factors associated with 1‐year mortality. Conclusions: In patients developing IE after transcatheter aortic valve replacement, mortality was predicted by the severity of IE and concomitant mitral regurgitation. In this small, and therefore statistically limited, but high‐risk patient cohort, CS provided no significant mortality benefit compared with medical therapy. Individual decision making by a "heart and endocarditis team" is necessary to offer those patients the most reasonable treatment option.